Electrokinetic power generation driven by forward osmosis - Hon, Kar Cherng (2014)
In this project, an unprecedented technique by leveraging the synergy of forward osmosis (FO) and electrokinetic (EK) phenomena for generating direct electricity (or power interchangeably) is developed and thoroughly studied. The source of the energy comes from the chemical potential difference between a pair of solutions of different concentration. To harvest the enormous source from nature, salinity gradient presented between fresh river and seawater is identified as the targeted source which leads to conceiving the concept of FO-EK energy harvesting technique from salinity gradient. In this concept of power generation, direct electricity is electrokinetically generated in the forms of streaming potential and streaming current with the much required hydrodynamic flows generated by the FO process. Both EK and FO are classified as interfacial phenomena and do not contain any mechanical moving parts in the system. In addition, the extra pumping requirement is excluded and replaced by FO process to avoid involvement of sophisticated machineries. Apparently, the entire power generation process is emission free without any pollution to the environment i.e. a sustainable technology.